IMPROVING THE QUALITY OF RELIGIOUS TEACHING THROUGH RELIGIOUS TEACHERS' INFORMATION AND ADMINISTRATION SYSTEMS (SIAGA) - Gobel, Syafiga Nurcahyani; Tui, Fenti Prihatini; Nani, Yacob Noho (Universitas Negeri Gorontalo, 2024)
This study aims to determine (1) the Application of Information Systems and Administration of Religious Teachers in the Regional Office of Gorontalo Province, (2)The Factors that Determine the Success of the Implementation of the Religious Teacher Information and Administration System (SIAGA) at the Regional Office of the Ministry of Religion of Gorontalo Province can be seen from several indicators such as being accurate, timely, and relevant. The research method used is a qualitative approach with a descriptive research type. Data collection techniques namely, interviews, observation, and documentation. Based on the results of the study, (1) the process of implementing the religious teacher information and administration system (SIAGA) at the regional office of the Gorontalo province can be seen from several aspects, namely the form of application for implementing tasks, governance, and technology that has been implemented properly. However, in using the SIAGA application, some obstacles are found, such as the network, when the network has problems, it will be difficult for them to upload data. (2) the factors that determine the success of implementing the religious teacher information and administration system (SIAGA) at the regional office of the Ministry of Religion in Gorontalo province include several aspects, namely accurate, timely, and relevant. It can be seen that it has been implemented properly.